THE IMPACT OF MICROFINANCE ON WOMEN’S PRODUCTIVITY: EVIDENCE FROM HAWASSA CITY, ETHIOPIA - Tedla, Hiwot; Chawla, Arvinder Singh (ShodhKosh: Journal of Visual and Performing Arts, 2026)
Background: Microfinance has been identified as a key component of poverty alleviation and gender equity policies in sub-Saharan Africa, but there is a lack of rigorous evidence that links access to credit with enterprise-level productivity outcomes for women entrepreneurs in urban Ethiopian settings. Objective: The objective of this study is to estimate causal impact of microfinance access on the productivity of women’s enterprises in Hawassa City, Ethiopia, and to investigate whether the provision of integrated business training services can enhance such impacts. Methods: This study employed primary survey data from 384 women entrepreneurs (213 treated and 171 control group members). Propensity Score Matching (PSM) using three different algorithms: nearest-neighbour (NNM), kernel (KBM) and radius (RM) methods, accounted for observable selection bias. Endogenous Switching Regression (ESR) also accounted for unobservable heterogeneity. The exclusion restriction was the geographical distance to the closest MFI branch. Results: Estimates of PSM-NNM show that participants experienced a statistically significant 34.7% increase in value added per worker (ATT = 1,462 ETB/month, p < 0.01) and 28.3 percentage points higher sales-revenue growth compared to controls. ESR results also validated these results (ATT = 31.2%, p < 0.01). Adding credit with business training further increased productivity by an additional 15.5 percentage points. Conclusions: Microfinance access has a significant positive effect on the productivity of women’s enterprises in urban Ethiopia. The greatest productivity gains can be realized when credit is combined with business development training.